THE ROLE OF STATISTICS IN DECISION MAKING - Subakti, Jani; Wibowo, Agung; Faizal, Harun (Manager : Jurnal Ilmu Manajemen, 2024)
In everyday life, every human being is faced with problems where he must make decisions. Starting from simple things such as deciding to extend the morning sleep time with all the risks that will be faced, to difficult and even complex things. These decisions can be personal or social or short-term or long-term that inevitably must be decided. This study uses the literature review method and in discussing several theories used, case studies are conducted. Every decision-making will always face four conditions, namely Certainty, Uncertainty, Risk and Conflict. The EV value is obtained from the multiplication of Payoff with its probability. The largest EV value is the decision that must be taken. The EOL results show that the lowest is C, so stock C can be recommended for purchase by investors such as case 1. From the EVPI value of 108,056, the cost for analysts is 21,611, investors still get additional profit of Rp86,445 compared to if investors do not get perfect information. A high EV value is the best decision. (b) paying attention to the best opportunity loss (expected opportunity loss – EOL). The value with the lowest EOL is the best decision, (c) paying attention to perfect information (expected value of perfect information – EVPI). EVPI pays attention to the perfect information factor so that it can optimize the level of profit